Managing Financial Sector Risks from the COVID-19 Crisis in the Caucasus and Central Asia - Ruxandra Teodoru, Iulia (Departmental Papers; Departmental Paper ;, 2022)
The COVID-19 crisis raises the risk of renewed financial sector pressures in the Caucasus and Central Asia (CCA) region in the period ahead. Bank distress and its economic and fiscal fallout have been recurring features of many CCA countries, as seen after the global financial crisis and the 2014-15 oil price shock. Strong policy responses have delayed the full impact of the COVID crisis so far, but financial sector risks will increase once public support is phased out. If these risks are not preemptively addressed, banks' ability to lend during the recovery phase could be impaired and there may be a need for costly public interventions, as in the past.